Use of Iron (II) Salts and Complexes for the Production of Soil Amendments from Organic Solid Wastes - Amerigo Beneduci; Ilaria Costa; Giuseppe Chidichimo (International Journal of Chemical Engineering)
A method to obtain rapidly stabilized composts for crops from solid organic wastes is evaluated. Here we used a laboratory scale reaction chamber where solid waste treatment was performed under strictly controlled temperature and pressure conditions. The row organic waste was mixed with acid solutions containing iron (II) ions either in the fully hydrated form or in the form of complexes with the diethylentriaminopentaacetic acid. Data from elemental analysis distribution and GC/MS analysis of the polar and non polar dissolved organic matter, clearly showed that Fe(II) ions significantly enhance organic substrate oxidation of the initial solid waste, compared to a material obtained without the addition of the Fe(II) ions to the raw organic matrix. These results suggest that Fe(II) ions might be involved in a catalytic oxidation pathway that would be activated under the experimental conditions used. The extent of the oxidation process was evaluated by the value of the C/N ratio and, qualitatively, by the molecular composition of the dissolved organic matter. After about 6 hours of incubation, dark-brown and dry organic matrices were obtained with C/N ratio as low as 12 and a high degree of oxidative decomposition into low-molecular-weight compounds at high oxidation state.